Description of eight new species and re-description of four species belonging to the family Phytoseidae (Acari: Mesostigmata) from West Bengal, India - Karmakar, Krishna; Bhowmik, Sagarika (Zootaxa, 2018)
This paper reports on 12 species of Phytoseiidae (Acari: Mesostigmata) from West Bengal, India. Amblyseius crotalariae (Gupta, 1977), Amblyseius guajavae (Gupta, 1978), Typhlodromips syzygii (Gupta, 1975), Scapulaseius asiaticus (Evans, 1953) are re-described, and Scapulaseius moraesi sp. nov., Euseius sundarbanensis sp. nov., Euseius astrictus sp. nov., Asperoseius latericulus sp. nov., Asperoseius jujubae sp. nov., Typhlodromus (Anthoseius) carambolae sp. nov., Typhlodromus (Anthoseius) heliotropium sp. nov. and Phytoseius namkhanaensis sp. nov. are described as new.